The breach of the air traffic safety or exploitation of air transport rules (art. 276 of Criminal Code of Ukraine): scientific and practical commentary - Багіров, Сергій Рамізович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Deep scientific and practical commentary of elements of the crimes that are contained in the art. 276 of Criminal Code of Ukraine, is done in the article. The emphasis is put on the disclosure of subjective and objective sides of the crimes, concerning only air transport. A social dependence of criminal forbiddance of certain acts is determined. A social danger of a crime provided in the art. 276 of Criminal Code of Ukraine is defined. The main direct and additional direct objects of this crime are analyzed; a mechanism of causing damage to the social relations as a result of its commitment is also disclosed. The author specifies the list and the features of the subject of the offence. In accordance with the Air Code of Ukraine, the content of such subjects of the crime as instruments of communication, navigation and surveillance (radio engineering support), is explored. It’s pointed out that a criminal-legal characteristic of the objective side depends on the kind of a complex of crime’s components that are defined in p. 1 art. 276 of the Criminal Code of Ukraine. The author distinguishes 3 types of such crimes: 1) the breach of the air traffic safety rules by the employee of the air transport; 2) the breach of the exploitation of air transport safety rules by the employee of the air transport; 3) poor quality repair of vehicles, tracks, alarm system and communication tools. The features of dangerous consequences of crime are revealed.